2020
DOI: 10.1101/2020.03.19.998740
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The pregnant myometrium is epigenetically activated at contractility-driving gene loci prior to the onset of labor in mice

Abstract: 25During gestation, uterine smooth muscle cells transition from a state of quiescence to one of 26 contractility, but the molecular mechanisms underlying this transition at a genomic level are not well-27 known. To better understand these events, we evaluated the epigenetic landscape of the mouse 28 myometrium during pregnancy, labor and post-partum. We established gestational timepoint-specific 29 enrichment profiles involving histone H3K27 acetylation (H3K27ac), H3K4 tri-methylation (H3K4me3), 30 and RNA pol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…Nevertheless, much recent work shows promise in the targeting of genomic activity in SMCs in order to prolong pregnancy. For instance, our earlier study uncovered gestational time point-specific, genome-wide active histone mark patterns; these patterns support previous findings that the onset of labor is associated with global histone deacetylation [8,26,27]. Recently, Zierden and others have developed a mode of delivery of suspensions containing inhibitors of histone deacetylase proteins alongside the labor-stalling hormone, progesterone; their results showed that these two-target suspensions provide greater efficacy in preterm birth prevention in bacterial infection-induced mouse labor models than two prominent approved drugs [28].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Nevertheless, much recent work shows promise in the targeting of genomic activity in SMCs in order to prolong pregnancy. For instance, our earlier study uncovered gestational time point-specific, genome-wide active histone mark patterns; these patterns support previous findings that the onset of labor is associated with global histone deacetylation [8,26,27]. Recently, Zierden and others have developed a mode of delivery of suspensions containing inhibitors of histone deacetylase proteins alongside the labor-stalling hormone, progesterone; their results showed that these two-target suspensions provide greater efficacy in preterm birth prevention in bacterial infection-induced mouse labor models than two prominent approved drugs [28].…”
Section: Discussionsupporting
confidence: 88%
“…Accordingly, we generated another reporter construct under the control of the endogenous murine Fos promoter. The genomic region upstream of this gene was selected in particular because of the previously observed up-regulation of Fos gene transcription in myometrial cells; the established role of FOS protein in driving labor-associated gene promoter activation; and on account of our previous findings that the Fos locus exhibits signs of elevated active transcription during active murine labor relative to late pregnancy [8,11,15,16]. Before testing the effects of either ELF3 or MYB on Fos promoter activity, however, unlike the case of the Gja1 promoter, the effects of JUN or FOS factors on this promoter had not yet been established in a myometrial context.…”
Section: Ap-1 Factors Positively Auto-regulate the Fos Promoter In My...mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, we performed cesarean delivery during uncomplicated labor to facilitate sample collection. This line of thought is supported by the 4-5-fold increased myometrial expression of OxtR gene during uncomplicated labor in rodents(37, 38).…”
Section: Commentmentioning
confidence: 88%